Numerals Variation of Gebe Language in Central Halmahera Regency: Morphosyntactic Study - Jalaluddin, Nurain; Maulud, Ismail (CV. Eureka Murakabi Abadi, 2025)
This research investigates the variation of numerals in the Gebe language, spoken in the Central Halmahera Regency, with a focus on its morphosyntactic structure. The study aims to describe how numeral forms vary and function within the grammatical framework of the language, particularly regarding noun phrases, classifiers, and verb agreement. Utilizing a descriptive qualitative method, data were collected through interviews, observation. and direct elicitation from native speakers across several Gebe-speaking communities. The analysis reveals that almost any type of noun, numeral, or described thing can exhibit this variety, although ordinal numerals offer fewer choices. These findings contribute to the documentation of the Gebe language and offer insights into the typological diversity of numeral systems in Eastern Indonesian languages. This study concludes that the numeral system of the Gebe language exhibits unique morphosyntactic characteristics, including variation in form, structure, and function, which not only differ based on semantic domains, such as human, non-human, and object counting, but also undergo specific morphological processes like affixation depending on the syntactic environment.